2009
DOI: 10.1002/jcp.21800
|View full text |Cite
|
Sign up to set email alerts
|

Gadd45a stress signaling regulates sFlt‐1 expression in preeclampsia

Abstract: Preeclampsia, which affects approximately 5-8% of all pregnancies and is one of the leading causes of maternal and fetal morbidity and mortality, is a pregnancy induced complex of multiple pathological changes, including elevated blood pressure, proteinuria and edema manifested after 20 weeks gestation. There is growing evidence that placental stresses during pregnancy, notably hypoxia, and an increase in circulating soluble Flt-1 (sFlt-1) are important in the etiopathogenesis of preeclampsia. How placental st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 26 publications
6
39
2
Order By: Relevance
“…Although Xiong et al (2009) have demonstrated that Gadd45α expression and the activation of its downstream effector p38 kinase are elevated in preeclamptic placentas compared with non-preeclamptic controls, the subjects in the previous study were American. Therefore, a repetition of these experiments in the Chinese population should make this study more rigorous and convincing.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Although Xiong et al (2009) have demonstrated that Gadd45α expression and the activation of its downstream effector p38 kinase are elevated in preeclamptic placentas compared with non-preeclamptic controls, the subjects in the previous study were American. Therefore, a repetition of these experiments in the Chinese population should make this study more rigorous and convincing.…”
Section: Introductionmentioning
confidence: 91%
“…In order to block the p38 MAPK pathway, HUVECs were pre-incubated with 5 μM SB203580 (Invitrogen, Carlsbad, Calif., USA), a specific inhibitor of p38 MAPK, 90 min before H/R exposure as previously described (Xiong et al 2009). SB203580 was dissolved in dimethyl sulfoxide (DMSO).…”
Section: Knockdown Of Gadd45α and P38 Mapk Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Human umbilical vein endothelial cells (HUVECs), cellular stress like hypoxia or IL-6 stimulation results in Gadd45a induction, p38 activation, and subsequently leads to the increase in sFlt-1 levels. 40 Also, when stimulating pregnant mice with serum from patients with preeclampsia, Zhou et al observed an increase in placental sFlt-1 expression that was blocked by pretreatment of the animals with an IL-6 neutralizing antibody. 25 This suggests a regulatory function of IL-6 in sFlt-1 production.…”
Section: Discussionmentioning
confidence: 99%